2002
DOI: 10.1002/ajmg.b.10031
|View full text |Cite
|
Sign up to set email alerts
|

Association of EEG coherence and an exonic GABABR1 gene polymorphism

Abstract: The GABA(B) receptor 1 gene is mapped to chromosome 6p21.3 within the HLA class I region close to the HLA-F gene. Susceptibility loci for epilepsy and schizophrenia have been mapped in this region. Based on pharmacological evidence, it has been suggested that GABA(B) receptors may play a crucial role in the synchronization of EEG oscillations, which in turn can be abnormal in neuropsychiatric disorders. In the present study, the hypothesis was tested, whether three exonic variants of the gene encoding the huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…Michael et al (1993) found higher central alpha and slowbeta coherence but lower parietal alpha and slow-beta coherence in male participants with alcohol dependence; contrarily, other findings suggest that morphine, alcohol, and marijuana show increased alpha 2 power in the spectral EEG and relate this to the euphoric state produced by the drug (Lukas, 1991(Lukas, , 1993Lukas et al, 1989Lukas et al, , 1995. Winterer, Enoch, et al (2003) and Winterer, Smolka, et al (2003) described higher lefttemporal alpha and slow-beta coherence and higher slow-beta coherence at right-temporal and frontal electrode pairs in alcoholdependent male and female participants. De Bruin et al (2004) showed that moderate to heavy alcohol consumption is associated with differences in synchronization of brain activity during rest and mental rehearsal.…”
Section: The Scott-kaiser Modification Of the Peniston Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Michael et al (1993) found higher central alpha and slowbeta coherence but lower parietal alpha and slow-beta coherence in male participants with alcohol dependence; contrarily, other findings suggest that morphine, alcohol, and marijuana show increased alpha 2 power in the spectral EEG and relate this to the euphoric state produced by the drug (Lukas, 1991(Lukas, , 1993Lukas et al, 1989Lukas et al, , 1995. Winterer, Enoch, et al (2003) and Winterer, Smolka, et al (2003) described higher lefttemporal alpha and slow-beta coherence and higher slow-beta coherence at right-temporal and frontal electrode pairs in alcoholdependent male and female participants. De Bruin et al (2004) showed that moderate to heavy alcohol consumption is associated with differences in synchronization of brain activity during rest and mental rehearsal.…”
Section: The Scott-kaiser Modification Of the Peniston Protocolmentioning
confidence: 99%
“…In addition, some genes coding for GABA receptors in the brain, which mediate the effects of alcohol, are related to certain EEG patterns (Porjesz et al, 2005;Winterer, Smolka, et al, 2003). Moreover, some GABA-receptor genes that are related to EEG patterns are also associated with the risk to develop alcohol dependence.…”
Section: Qeeg In Sudmentioning
confidence: 99%
“…In addition, some genes coding for GABA receptors in the brain, which mediate the effects of alcohol, are related to certain EEG patterns (e.g., Winterer et al, 2003c). Moreover, some GABAreceptor genes that are related to EEG patterns are also associated with the risk to develop alcohol dependence.…”
Section: Introductionmentioning
confidence: 99%
“…(1.4) [19,20,21]. They represent some join characteristic of the two channels involved in the computation.…”
Section: B Fourier Transformmentioning
confidence: 99%
“…The coherence measure quantizes the correlation between two time series at different frequencies [19,20]. The magnitude of the squared coherence estimate is a frequency function with values ranging from 0 to1.…”
Section: B Coherencementioning
confidence: 99%